Cash Waqf Management Perspective of Maqashid Shariah Ibn 'Asyr (UNISIA Cash Waqf Institution Study) - Navirta Ayu; Asmuni (Pascasarjana, Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2023)
This research is normativ research which is part of libery research. In this research we will examine cash waqf which is not far from the existing problem formulation. That is how the role of the UNISIA cash waqf institution in making cash waqf a success as well progress in developing the community’s economy? And what is the maqashid of cash waqf as a community empowerer from the perspective of Ibn’Assyria’s maqashid?. Results research shows that in indonesia itself it is allowed to exist cash waqf or cash waqf with the emergence of the MUI fatwa regarding cash waqf and the existence of statutory regulations such as the waqf law no. 41 of 2004 as well some other rules. The ull waqf board foundation also launched the institute UNISIA cash waqf of december 22 2021,which is expected to progress helping the community’s economy such as empowering MSMES, education, and other economic sectors of society. Maqashid based analysis Ibn’Asyur in this case shows that there are two maqashid carried out in cash practice. First, Maqashid khassah is in the form of hifz almal which makes waqf objects more productive. Second, maqashid ammah in the form of universal benefit in economic empowerment community allocated to education, health, places of worship and things other social.